Impact of comorbid pulmonary disease on COVID-19 disease severity and outcome: a retrospective cohort study - Sally Magdy; Reem Elkorashy; Eman Hany Elsebaie; Hebatallah Hany Assal; Hoda M. Abdel-Hamid (The Egyptian Journal of Bronchology, 2023)
Abstract Background Identifying patients with comorbid pulmonary disease may guide prognosis and aid in developing strategies regarding who would benefit the most from vaccines. This study was designed to clarify the influence of comorbid lung disease on COVID-19 severity and outcome. Methods This is a retrospective cohort analysis of 587 COVID-19 patients. The clinical, laboratory, and imaging data and comorbidities as reported by the patients were obtained from the Kasr Alainy Hospital medical records. Also, data regarding whether the patient is hospitalized or not, the length of hospital stay, complications, and mortality are gathered from the records. Results The patients’ mean ages are 51 ± 15 years (63.9% are males with the remaining 36.1% which are females). Patients with chronic comorbid pulmonary diseases represented 113 patients among the whole study population. with the COPD being 11.4%. Patients with comorbid lung diseases associated or not with other comorbidities were at higher risk of acquiring severe COVID-19 and had higher complication and mortality rates compared to patients without comorbidities (p-value < 0.001). Patients with preexisting diabetes, hypertension, COPD, and chronic kidney disease have a significantly higher risk of severe infection (p-value < 0.001, 0.001, 0.001, < 0.001), complications (p-value 0.038, 0.005, < 0.001, < 0.001), and mortality (p-value 0.021, 0.001, < 0.001, < 0.001), respectively. Conclusion This study provides a better understanding of COVID-19 patients with comorbid lung disease and highlights the importance of the data deduced from our study and similar studies in aiding the designation of vaccination programs for those patients if needed.